2014
DOI: 10.1364/oe.22.023339
|View full text |Cite
|
Sign up to set email alerts
|

Electro–optical tunable waveguide embedded multiscan Bragg gratings in lithium niobate by direct femtosecond laser writing

Abstract: optical tunable Bragg gratings in lithium niobate fabricated by direct femtosecond laser writing. The hybrid design that consists of a circular type-II waveguide and a multiscan type-I Bragg grating exhibits low loss ordinary and extraordinary polarized guiding as well as narrowband reflections in the c-band of optical communications. High bandwidth tunability of more than a peak width and nearly preserved electro-optic coefficients of r(13) = 7.59 pm V(-1) and r(33) = 23.21 pm V(-1) are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 29 publications
0
43
0
3
Order By: Relevance
“…In this case, the WBG refractive index contrast was photostable [68]. Waveguide lasers (WGLs) using this glass host showed a Multiscan WBGs were inscribed in lithium niobate very close to the threshold between types I and II modifications by Kroesen et al [49]. It was shown that, after thermal treatment at 250°C for 24 h, the WBG reflectivity decayed slightly; however, the spectral properties improved.…”
Section: Annealing Stabilitymentioning
confidence: 62%
See 4 more Smart Citations
“…In this case, the WBG refractive index contrast was photostable [68]. Waveguide lasers (WGLs) using this glass host showed a Multiscan WBGs were inscribed in lithium niobate very close to the threshold between types I and II modifications by Kroesen et al [49]. It was shown that, after thermal treatment at 250°C for 24 h, the WBG reflectivity decayed slightly; however, the spectral properties improved.…”
Section: Annealing Stabilitymentioning
confidence: 62%
“…For comparison, Table 1 lists κ values for The duty cycle was fixed at 35%, whereas the writing pulse energy was varied. [21] PbP 1551 25 -Boro-aluminosilicate (Eagle2000) [22] PbP 1551 145 0.6 Boro-aluminosilicate (Eagle2000) [23] PbP 1550 472 0.5 Soda-lime [27] Two-step PbP 1577 14 -Fused silica [26] Modulated burst 1548 111 1.5 Er:Yb codoped phosphate [30] Modulated burst 1537 242 -Yb-doped phosphate [42] Modulated burst 1535 221 -Boro-aluminosilicate (Eagle2000) [31] Modulated burst 1551 713 -Fused silica [43] Modulated burst 1546 36 0.7 Boro-aluminosilicate (Eagle2000) [24] PbP 799 65 -Boro-aluminosilicate (Eagle2000) [28] Modulated burst 1552 157 -ZBLAN [29] PbP überstructure 1550 324 -Boro-aluminosilicate (Eagle2000) [44] Multiscan modulated burst 1563 177 -LiNbO 3 [45] Modulated burst stressors 1540 45 -Boro-aluminosilicate (Eagle2000) [41] PbP 648 136 -Boro-aluminosilicate (Eagle2000) [41] PbP 698 183 0.8 Boro-aluminosilicate (Eagle2000) [41] PbP 748 187 -Boro-aluminosilicate (Eagle2000) [41] PbP 798 163 -Fused silica [46] Modulated burst 1550 210 2.2 Fused silica [47] Modulated burst 1549 280 < 1 Chalcogenide (GLS) [48] Modulated burst 1551 179 -LiNbO 3 [49] Multiscan modulated burst (depressed clad) 1558 1230 1.52-3.51 Boro-aluminosilicate (Eagle2000) [50] Two-step PbP 1545 120 -Fused silica [25] PbP (waveguide bundle) 840 126 -Fused silica [25] PbP (waveguide bundle) 1550 220 1.6 Borosilicate (AF45) [51] Modulated …”
Section: Coupling Coefficient κmentioning
confidence: 99%
See 3 more Smart Citations